Pelatihan Merancang Indikator Pencapaian Kompetensi (IPK) dan Tujuan Pembelajaran Berdasarkan Kurikulum 2013 bagi Guru-Guru Pemula Bahasa Inggris di SMP dan SMA. - Flora; Ujang Suparman; Tuntun Sinaga; Khairun Nisa (Jurusan Pendidikan Bahasa dan Sastra Indonesia, FKIP Universitas Lampung, 2023)
Pada kurikulum 2013 terdapat Kompetensi Dasar (KD). KD ini berfungsi sebagai acuan atau rujukan guru dalam menyusun indikator kompetensi pada pembelajaran di kelas. Indikator merupakan tanda yang menunjukkan bahwa tingkat capaian kompetensi dasar bisa mengubah perilaku peserta didik yang dinilai dari sikap, pengetahuan, dan keterampilannya. Indikator inilah sebagai rujukan dalam merumuskan tujuan pembelajaran. Selanjutnya tujuan pembelajaran adalah sebagai rujukan untuk mennentukan langkah-langkah pembelajaran. Sasaran pelatihan ini adalah guru-guru SMP dan SMA yang memiliki pengalaman kerja minimal maksimum 5 tahun dan belum mengikuti PPG sebanyak 20 orang. Students’ worksheet is nedeed since it can help the students to achieve the optimal learning objectives. However, based on the information gathered from the teachers’ association, most of the teachers never provide students’ worksheet. Therefore, this public service gave chance for SMA English teachers in Bandarlampung to create good students’ worksheet. This activity was lasted for 3 days, and the steps are ; 1) explaining the concept of students’ worksheet by giving the example of students’ workshet, 2) learning community, where the participants work in a small group to produce students’ worksheet based on provided learning objectives, 3) presenting the result by the representative of each group, and 4) individual task. This program showed that 6 participants (14%) were able to create students’ worksheet with very good catagory, 30 participants (72%) with good catagory, and 6 participants (14%) with good enough catagory. The participants were able to create students’ worksheet because they were directly given the example, and were discussed together with the tutor. By involving all students in learning community, they can share their ideas. In addition, presentation of each representative of each group made the participants have deeper understanding because they got input from peers and tutor.